LOKASI DAN PROMOSI MELALUI PENGETAHUAN KONSUMEN UNTUK MENINGKATKAN MINAT MENABUNG DI BANK SYARIAH - Nurul Hermina; Supriyadi, Cecep; Kusumawardana, Mohammad Fauzi (Ekonomi dan Bisnis, 2024)
Sharia Bank in West Java can only control the market by 10.8%, so the remaining 89.2% is still controlled by conventional banks. The low number of Sharia Bank customers indicates that buying interest or interest in saving at Sharia Bank can be said to be low. This research investigates how consumer knowledge mediates the influence of location and promotion on interest in saving at Sharia banks in Bandung City and Cimahi City. The object of this research is the respondents' perceptions of the Sharia Bank in Bandung City and Cimahi City. This research uses an explanatory quantitative approach based on deductive reasoning. The research strategy used in this research is a survey strategy with data processing using SPSS. The results of the research show that location has a positive and significant effect on consumer knowledge, promotion has a positive and significant effect on consumer knowledge, location has a positive and significant effect on interest in saving, promotion has a positive and significant effect on interest in saving, consumer knowledge has a positive and significant effect on interest in saving, location has a positive and significant effect on interest in saving which is mediated by consumer knowledge and promotion has a positive and significant effect on interest in saving which is mediated by consumer knowledge